Mindfulness Training, Cognitive Performance and Stress Reduction - Gary Charness; Yves Le Bihan; Marie Claire Villeval (Institute of Labor Economics (IZA), 2023)
Improving cognitive function and reducing stress may yield important benefits to individuals' health and to society. We conduct an experiment involving a three-month within-firm training program based on the principles of mindfulness and positive psychology at three large companies. We find an improvement in the difference-in-differences across the training and control groups in all five non-incentivized measures and in seven of the eight incentivized tasks but only the non-incentivized measures and one of the incentivized measures reached a standard level of significance (above 5%), showing strong evidence of its impact on both reducing perceived stress and increasing self-reported cognitive flexibility and mindfulness. At the aggregate level, we identify an average treatment effect on the treated for the non-incentivized measures and some effect for the incentivized measures. Remarkably, the treatment effects persisted three months after the training sessions ended. Overall, mindfulness training seems to provide benefits for psychological and cognitive health in adults.
Keywords: C91; I12; 330; mindfulness; attention; cognition; stress; lab-in-the-field experiment